ANALISIS HARGA POKOK JASA LAYANAN PERIKLANAN MELALUI MEDIA SOSIAL TWITTER - muhammad reza ramdani; Muhammad Ashoer (KRISNA: Kumpulan Riset Akuntansi, 2021)
Technology is becoming a lifestyle of society in the present era, internet lanes become one of the optional paths for people who are less able to compete in normal business traffic lanes. The purpose of the research to analyze the underlying price of advertising services perspectives cost classification in a business run by one on twitter social media. This research approach is done by quantitative descriptive, The type of data used in the form of cost reports on makassar promo twitter account. Data analysis is done by selling price determination method, to find out how much is appropriate for each ad. The results showed that there has not been a classification of costs carried out by makassar promo accounts, so there is a burden that is not taken into account in the study of the basic price of services.